Intracerebral endotheliitis and microbleeds are neuropathological features of COVID‐19. (14th December 2020) - Kirschenbaum, Daniel; Imbach, Lukas L.; Rushing, Elisabeth J.; Frauenknecht, Katrin B. M.; Gascho, Dominic; Ineichen, Benjamin V.; Keller, Emanuela; Kohler, Sibylle; Lichtblau, Mona; Reimann, Regina R.; Schreib, Katharina; Ulrich, Silvia; et al.
Abstract: Coronavirus disease 19 (COVID‐19) is a rapidly evolving pandemic caused by the coronavirus Sars‐CoV‐2. Clinically manifest central nervous system symptoms have been described in COVID‐19 patients and could be the consequence of commonly associated vascular pathology, but the detailed neuropathological sequelae remain largely unknown. A total of six cases, all positive for Sars‐CoV‐2, showed evidence of cerebral petechial hemorrhages and microthrombi at autopsy. Two out of six patients showed an elevated risk for disseminated intravascular coagulopathy according to current criteria and were excluded from further analysis. In the remaining four patients, the hemorrhages were most prominent at the grey and white matter junction of the neocortex, but were also found in the brainstem, deep grey matter structures and cerebellum. Two patients showed vascular intramural inflammatory infiltrates, consistent with Sars‐CoV‐2‐associated endotheliitis, which was associated by elevated levels of the Sars‐CoV‐2 receptor ACE2 in the brain vasculature. Distribution and morphology of patchy brain microbleeds was clearly distinct from hypertension‐related hemorrhage, critical illness‐associated microbleeds and cerebral amyloid angiopathy, which was ruled out by immunohistochemistry. Cerebral microhemorrhages in COVID‐19 patients could be a consequence of Sars‐ CoV‐2‐induced endotheliitis and more general vasculopathic changes and may correlate with an increased risk of vascular encephalopathy. Abstract : Clinically manifest central nervous system symptoms are common in COVID‐19 patients but their causes are still unknown. We present here four patients who tested positive for Sars‐CoV‐2 with cerebral haemorrhages which were most prominent at the grey and white matter junction of the neocortex and the brainstem. We present evidence of intracerebral endotheliitis in COVID‐19 patients which could predispose to more general vasculopathic changes and may correlate with an increased risk of vascular encephalopathy.